Development of a Web-Based IoT Class Attendance Monitoring System for a Primary School - Kamaruddin, Siti Sazleena; Alduais, Nayef Abdulwahab Mohammed (Applied Information Technology And Computer Science, 2024)
The Web-Based Attendance Monitoring System is designed to efficiently track attendance for students, teachers, and staff at Sekolah Kebangsaan Abdullah. Currently, the school relies on manual methods, using paper for student attendance and punch cards for teachers and staff. This outdated process leads to inaccuracies in attendance records. The project was developed a Web-Based IoT Class Attendance Monitoring System for Primary Schools, employing the Waterfall Model for effective project management. The system, developed on a web-based platform, integrates RFID components with IoT, utilizing Arduino IDE and Visual Studio Code for testing. The integration of RFID with IoT provides real-time attendance data. With a functionality testing and User Acceptance Test (UAT), it focuses on ensuring that all features work correctly and that the software behaves as intended. The absence of user validation after registration that can be resolved by incorporating extra security measures and linking the system with a front-end website.